Evaluation of bacteriological indicators of disinfection for alkaline treated biosolids. Issue 4 (1st July 2004) - Meckes, Mark C; Rhodes, Eric R
Abstract : A suite of methods was used to enumerate fecal coliforms, total culturable heterotrophs, Escherichia coli ( E. coli ), Clostridium perfringens endospores ( C. perfringens ), aerobic endospores, and Salmonella spp. in untreated municipal sludge and lime treated biosolids. Results of this work indicate that the fecal coliform methods used during this evaluation were not significantly different (α = 0.05). Similarly the E. coli methods were also shown to be not significantly different (α = 0.05). We also found that the fecal coliform and E. coli populations are more susceptible to lime treatment than other heterotrophic bacteria. Endospore forming bacteria were found to survive lime treatment while the numbers of other indicator organisms were significantly reduced. Finally, we showed that the density of aerobic endospores and their resistance to lime treatment was comparable to the densities and resistance of C. perfringens endospores in both Class A and B alkaline treated biosolids. Key words : biosolids, fecal coliform, salmonellae, Escherichia coli, Clostridium perfringens endospores, aerobic endospores, sludge, lime, disinfection.